The Relationship between Stroke Patients Characteristics and Family Support with Compliance Rehabilitation - Irma Okta Wardhani; Santi Martini (Universitas Airlangga, 2015)
Stroke is a cerebrovascular disease that affects paralysis. Family support is something that needs to be considered in the handling of stroke patients because it is very instrumental in the compliance of patients undergoing rehabilitation to prevent stroke recurrent. Characteristics of stroke patients can also affect patient compliance in undergoing rehabilitation. The purpose of this study was to determine the relationship between the characteristics of stroke patients and family support with adherence to undergo rehabilitation in the Medical Rehabilitation Unit of the Haji Public Hospital in Surabaya. This research was an analytic observational with cross-sectional design. Samples were taken with a total population technique, as many as 22 respondents. The independent variable in this study was family support. The dependent variable is rehabilitation compliance. The results of the study are presented in the form of frequency distribution and calculate the strength of the relationship by looking at the coefficient Phi. The results of this study are that there is a strong relationship between family support and adherence to undergo rehabilitation (r = 0.582). There was a weak relationship between age (r = -0.027), sex (r = 0.092), level of education (r = -0.295), occupation (r = 0.098), and marital status (r = 0.319) and adherence to rehabilitation. Based on the results of the study, it can be concluded that family support can affect the compliance of stroke patients in undergoing rehabilitation.